'My life is like a massive jigsaw with pieces missing'. How 'lower-attaining' children experience school in terms of their well-being. Issue 8 (17th November 2021) - Buchanan, Denise; Hargreaves, Eleanore; Quick, Laura
ABSTRACT: 'Lower-attaining' children are known to encounter negative experiences in school, including experiencing feelings of upset, shame and inferiority. Using extensive interview and observation data from the first two years of a five-year longitudinal study of 23 'lower-attaining' children (age 7–9), we draw on Seligman's theory of well-being to identify the children's experiences of school in terms of their emotions, relationships and sense of achievement. Our analysis finds that on balance, these children are experiencing threats to their well-being in relation to their perceived lack of attainment and its associated shame, in an increasingly performative educational culture. We conclude that such threats are hampering the well-being of these children, which may cause both immediate and longer-term damage.